The impact of community services usage on geriatric depression: a ten-year follow-up study - Li, Xiaowen; He, Yuanqing; Chen, Shuhu; Zhang, Jun (BMC geriatrics, 2024)
This study explores whether the impact of environmental factors (community services usage, CSU) on geriatric depression is mediated by psychological resilience and moderated by the COMT (catechol-O-methyltransferase) gene val158met polymorphism. The data consists of 13,512 entries from the Chinese Longitudinal Healthy Longevity Survey (CLHLS) collected in the years 2008, 2011, 2014, and 2018. The study employed a Random Intercept Cross-Lagged Panel Model (RI-CLPM) to examine the relationship between CSU and geriatric depression, including the mediating effect of psychological resilience and the moderating role of the comt gene val158met gene polymorphism in this relationship. Lower CSU at earlier assessments were significantly associated with more severe geriatric depression in subsequent evaluations.Psychological resilience was found to partially mediate the relationship between CSU and depression.Differential impacts were observed among various gene genotypes; specifically, the val genotype demonstrated a significantly greater influence of CSU on subsequent psychological resilience and on subsequent depression compared to the met genotype. Enhancement in CSU can predict subsequent geriatric depression. The relationship between the CSU and depression can be mediated by psychological resilience, with genetics modulating the pathway from CSU through psychological resilience to depression. Multidisciplinary interventions focused on enhancing community service quality, boosting psychological resilience, and mitigating depression are likely to benefit the older adults's emotional and psychological well-being.